Thrombosis in the critically ill neonate: incidence, diagnosis, and management - Alex Veldman (Vascular Health and Risk Management, 2008)
Alex Veldman1, Marcel F Nold2, Ina Michel-Behnke31Monash Newborn and Ritchie Centre for Baby Health Research, Monash Medical Centre and Monash Institute of Medical Research, Melbourne, VIC, Australia; 2Dept of Medicine, University of Colorado Health Sciences Center, Denver, CO, USA; 3Dept of Pediatric Cardiology, Pediatric University Hospital, Vienna, AustriaAbstract: Among children, newborn infants are most vulnerable to development of thrombosis and serious thromboembolic complications. Amongst newborns, those neonates who are critically ill, both term and preterm, are at greatest risk for developing symptomatic thromboembolic disease. The most important risk factors are inflammation, DIC, impaired liver function, fluctuations in cardiac output, and congenital heart disease, as well as exogenous risk factors such as central venous or arterial catheters. In most clinically symptomatic infants, diagnosis is made by ultrasound, venography, or CT or MRI angiograms. However, clinically asymptomatic vessel thrombosis is sometimes picked up by screening investigations or during routine imaging for other indications. Acute management of thrombosis and thromboembolism comprises a variety of approaches, including simple observation, treatment with unfractionated or low molecular weight heparin, as well as more aggressive interventions such as thrombolytic therapy or catheter-directed revascularization. Long-term follow-up is dependent on the underlying diagnosis. In the majority of infants, stabilization of the patients’ general condition and hemodynamics, which allows removal of indwelling catheters, renders long-term anticoagulation superfluous. Nevertheless, in certain types of congenital heart disease or inherited thrombophilia, long-term prophylaxis may be warranted. This review article focuses on pathophysiology, diagnosis, and acute and long-term management of thrombosis in critically ill term and preterm neonates.Keywords: thrombosis, neonate, pathophysiology, diagnosis, therapy